2005
DOI: 10.1007/s00520-005-0846-z
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture against chemotherapy-induced nausea and vomiting in pediatric oncology

Abstract: Our data indicate that acupuncture might reduce antiemetic medication and episodes of vomiting in pediatric oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 13 publications
1
63
0
3
Order By: Relevance
“…In the immediate acupuncture group, initial improvements in pain scores did not persist six weeks after they completed acupuncture treatment. Similarly, other acupuncture studies which have implemented a cross-over design did not find evidence of carryover effects of acupuncture [59][60][61]. However, the sample sizes were small and the follow-up was short, and it would be premature to speculate about the long-term effects of acupuncture, since most studies do not assess patients following the intervention.…”
Section: Discussionmentioning
confidence: 89%
“…In the immediate acupuncture group, initial improvements in pain scores did not persist six weeks after they completed acupuncture treatment. Similarly, other acupuncture studies which have implemented a cross-over design did not find evidence of carryover effects of acupuncture [59][60][61]. However, the sample sizes were small and the follow-up was short, and it would be premature to speculate about the long-term effects of acupuncture, since most studies do not assess patients following the intervention.…”
Section: Discussionmentioning
confidence: 89%
“…Study investigators noted that acceptance of acupuncture among this young population was high, and acupuncture aided in higher levels of alertness during chemotherapy. 15 Nausea and vomiting are also a significant side effect after postoperative procedures with local or systemic anesthesia. Within 24 hours of surgery, pediatric patients experience postoperative nausea and vomiting (PONV) in 30% to 80% of cases.…”
Section: Nausea and Vomitingmentioning
confidence: 99%
“…It is significant, however, that although acupuncture on children has been shown to be feasible and acceptable, 50,[52][53][54] and children have shown little discomfort or fear, only 5 recent studies on the effectiveness of acupuncturepoint stimulation for CINV have included pediatric subjects. 45,[55][56][57] Cohen 58 has suggested that, to provide the best possible care, the physician balance 7 important factors when deciding whether to recommend a CAM treatment: (1) severity and acuteness of the illness; (2) curability with conventional treatment; (3) invasiveness, toxicities, and adverse effects of conventional treatment; (4) quality and evidence of safety and efficacy of the CAM treatment; (5) degree of understanding of the risks and benefits of conventional and CAM treatments; (6) knowledge and voluntary acceptance of those risks by the patient; and (7) persistence of the patient's intention to use CAM.…”
Section: Clinical Responsementioning
confidence: 99%